CREATIVE WAYS TO MAKE ENGLISH LEARNING ENGAGING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores a variety of innovative and engaging strategies for making English language learning more interactive and engaging for students. By incorporating methods such as task-based learning, the use of technology and apps, project-based assignments, and creative activities such as storytelling and music, teachers can create a dynamic and motivating learning environment for students. The article highlights the importance of adapting lessons to real-life contexts and integrating art and creative expression into language learning. These methods not only increase students’ language skills, but also their enthusiasm and confidence in English. The aim is to highlight practical and engaging approaches that are adapted to different school settings, and to increase the effectiveness and enjoyment of English language learning.